Natural Durability and Apparent Specific Weights of Acrocarpus fraxinifolius Wight & Arn (Pink Cedar) Cultivated in the Province of Misiones, Argentina. (2015) - Suirezs, T.; Arenhardt, O.; Stehr, A.; Bobadilla, E.; Weber, E.; Bragañolo, A.
Abstract: The objectives of this study were to explore the natural durability of heartwood and sapwood facing the action of the fungus Laetiporus sulphureus BAFC: 205, and also to determinetheapparent specific weightsof twelve years old Acrocarpus fraxinifolius Wight & Arn tree woods (Pink cedar), grown in Misiones, Argentina. The selected trees werefelledand sectionedinto logs, then sawed into strips from which the samples were obtained in order to carry out the durability testing following the modified European Norm N o 113, and the apparent specific weight using theIRAM Argentine Norm No.9544. The results showed that heartwood is non-resistant, sapwood is perishable, and also according to the apparent specific weight it must be classified as half-heavy wood.We conclude that the A. fraxinifolius wood can be used mainly for interior constructions and for furniture.